2019
DOI: 10.1111/mmi.14357
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Toxoplasma gondii mitochondrial ribosome, and characterisation of a protein essential for mitochondrial translation

Abstract: Summary Apicomplexan parasites cause diseases such as malaria and toxoplasmosis. The apicomplexan mitochondrion shows striking differences from common model organisms, including fundamental processes such as mitochondrial translation. Despite evidence that mitochondrial translation is essential for parasite survival, it is largely understudied. Progress has been restricted by the absence of functional assays to detect apicomplexan mitochondrial translation, a lack of knowledge of proteins involved in the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(85 citation statements)
references
References 74 publications
6
78
1
Order By: Relevance
“…Apicomplexan infectious zoites such as Toxoplasma tachyzoites have a robust cell pellicle (Figure 1A) that is resistant to simple cell disruption by hypotonic lysis. Nitrogen cavitation (Lacombe et al, 2019;Wang et al, 2014) was identified as the most effective, as well as non-heat-generating, method of cell disruption (Table S1). Membranous compartments and other cell particles were enriched from soluble cytosolic material by discontinuous density centrifugation of the homogenate, and this particulate material was then fractionated on continuous linear density gradients of iodixanol resulting in distinct enrichment profiles for a broad range of organelle markers (Figure 1B).…”
Section: Whole-cell Biochemical Fractionation Of Toxoplasma Gondii Exmentioning
confidence: 99%
See 1 more Smart Citation
“…Apicomplexan infectious zoites such as Toxoplasma tachyzoites have a robust cell pellicle (Figure 1A) that is resistant to simple cell disruption by hypotonic lysis. Nitrogen cavitation (Lacombe et al, 2019;Wang et al, 2014) was identified as the most effective, as well as non-heat-generating, method of cell disruption (Table S1). Membranous compartments and other cell particles were enriched from soluble cytosolic material by discontinuous density centrifugation of the homogenate, and this particulate material was then fractionated on continuous linear density gradients of iodixanol resulting in distinct enrichment profiles for a broad range of organelle markers (Figure 1B).…”
Section: Whole-cell Biochemical Fractionation Of Toxoplasma Gondii Exmentioning
confidence: 99%
“…In Toxoplasma, previous efforts to identify new candidate proteins for select compartments have used the correlation of transcript abundance profiles across the cell cycle making the assumption that co-located proteins are coexpressed (Bai et al, 2018;Lacombe et al, 2019;Long et al, 2017;Sheiner et al, 2011). However, an objective assessment of the coordination of gene expression for compartment proteins has not been previously possible without comprehensive knowledge of the spatial distribution of the proteome.…”
Section: Some But Not All Compartments Show Tight Transcriptional Rmentioning
confidence: 99%
“…We showed that knockdown of the conserved mitoribosomal LSU protein, PfmtRPL13 (PF3D7_0214200), caused a loss of ∆Ѱm, followed by parasite death (36). The essential nature of the mitoribosome in Toxoplasma gondii, another apicomplexan parasite, has also been reported (38). However, there is no literature on any of 14 annotated SSU proteins in Plasmodium (www.PlasmoDB.org).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significance of mtETC in apicomplexan parasites, few studies have been done to understand mechanisms of mitochondrial protein translation. It was only recently demonstrated that the mitoribosome is absolutely essential in these parasites (36,38). In addition, we found that mitochondrial protein translation is not only critical for maintenance of mitochondrial functions, but is also important to keep the integrity of the growing MIM as the parasite matures (36).…”
Section: Discussionmentioning
confidence: 75%
“…In addition, 3 extra annotated SSU proteins in Plasmodium (S22, S29, and S35) have no bacterial homologs; hence, the positions of these three were not predicted. Recent work on Toxoplasma gondii, another apicomplexan parasite, showed that TgmS35 (TGME49_203620) is localized in the parasite mitochondrion and is essential for parasite growth (38). From the list of 14 Plasmodium SSU proteins, in this study, we chose to work with three putative proteins: primary (PfmtRPS17, PF3D7_1365100), secondary (PfmtRPS18, PF3D7_1211500) and tertiary (PfmtRPS12, PF3D7_0412100).…”
Section: A Predicted Map Of the Plasmodium Mitoribosome Ssumentioning
confidence: 99%